PREPARATIVE ISOLATION AND PURIFICATION OF PRENYLATED ISOFLAVONOIDS FROM CUDRANIA TRICUSPIDATA FRUITS USING CENTRIFUGAL PARTITION CHROMATOGRAPHY - Jeon, Je-Seung; Kim, Sang-Min; Lee, Hee Ju; Um, Byung Hun; Kim, Hak Ki; Kim, Chul Young (TAYLOR & FRANCIS INC, 2012)
Prenylated isoflavonoids such as 6,8-diprenylorobol, 6,8-diprenylgenistein and 4'-O-methylalpinumisoflavone were purified from n-hexane extract of C. tricuspidata fruits using centrifugal partition chromatography (CPC) with a n-hexane-ethyl acetate-methanol-water (7: 3: 6: 4, v/v, ascending mode) solvent system in a one-step within 200 min. One-step preparative CPC yielded 22.4 mg of 6,8-diprenylorobol and 26.7 mg of 6,8-diprenylgenistein with 95% and 85% purity, respectively, from 350 mg of crude hexane extract. Further purification by crystallization in methanol yielded 4'-O-methylalpinumisoflavone (9.3 mg) at over 95% purity based on the HPLC analysis. The chemical structures of purified compounds were elucidated by H-1, C-13 NMR, and ESI-MS.
Keywords: XANTHONES; FLAVONOIDS; CONSTITUENTS; ANTIOXIDANT; SEPARATION